Follicle-Stimulating Hormone Induces Lipid Droplets via Gαi/o and β-Arrestin in an Endometrial Cancer Cell Line - Sayers, Niamh S.; Anujan, Priyanka; Yu, Henry N.; Palmer, Stephen S.; Nautiyal, Jaya; Franks, Stephen; Hanyaloglu, Aylin C. (Frontiers in Endocrinology, 2022)
Follicle-stimulating hormone (FSH) and its G protein-coupled receptor, FSHR, represents a paradigm for receptor signaling systems that activate multiple and complex pathways. Classically, FSHR activates Galphas to increase intracellular levels of cAMP, but its ability to activate other G proteins, and β-arrestin-mediated signaling is well documented in many different cell systems. The pleiotropic signal capacity of FSHR offers a mechanism for how FSH drives multiple and dynamic downstream functions in both gonadal and non-gonadal cell types, including distinct diseases, and how signal bias may be achieved at a pharmacological and cell system-specific manner. In this study, we identify an additional mechanism of FSH-mediated signaling and downstream function in the endometrial adenocarcinoma Ishikawa cell line. While FSH did not induce increases in cAMP levels, this hormone potently activated pertussis toxin sensitive Galphai/o signaling. A selective allosteric FSHR ligand, B3, also activated Galphai/o signaling in these cells, supporting a role for receptor-mediated activation despite the low levels of FSHR mRNA. The low expression levels may attribute to the lack of Galphas/cAMP signaling as increasing FSHR expression resulted in FSH-mediated activation of the Gs pathway. Unlike prior reports for FSH-mediated Galphas/cAMP signaling, FSH-mediated Galphai/o signaling was not affected by inhibition of dynamin-dependent receptor internalization. While chronic FSH did not alter cell viability, FSH was able to increase lipid droplet size. The β-arrestins are key adaptor proteins known to regulate FSHR signaling. Indeed, a rapid, FSH-dependent increase in interactions between β-arrestin1 and Galphai1 was observed via NanoBiT complementation in Ishikawa cells. Furthermore, both inhibition of Galphai/o signaling and siRNA knockdown of β-arrestin 1/2 significantly reduced FSH-induced lipid droplet accumulation, implying a role for a Galphai/o/β-arrestin complex in FSH functions in this cell type. As FSH/FSHR has been implicated in distinct hormone-dependent cancers, including endometrial cancer, analysis of the cancer genome database from 575 human endometrial adenocarcinoma tumors revealed that a subpopulation of samples expressed FSHR. Overall, this study highlights a novel mechanism for FSHR signal pleiotropy that may be exploited for future personalized therapeutic approaches.